Terror and Pity Aleksandr Sumarokov and the Theater of Power in Elizabethan Russia. (Imperial encounters in Russian history., 2016)
Situated on the intersection of comparative literary criticism, political history and theory, and cultural analysis, Terror and Pity: Aleksandr Sumarokov and the Theater of Power in Elizabethan Russia offers an in-depth reading of early Russian tragedy as a political genre. Imported to Russia by Aleksandr Sumarokov around 1750, tragedy reenacted and shaped the symbolic economy and the often disturbing historical experience of "absolutist" autocracy. Addressing half-forgotten texts and events, this study engages with literary and cultural theory from Walter Benjamin to Foucault and "new historicism" in order to contribute to a broader discussion of early modern "poetics of culture."